Pengaruh Desain Produk Dan Promosi Penjualan Terhadap Volume Penjualan Smartphone Samsung Studi Kasus Pada Mahasiswa Universitas Dharmawangsa Medan) - Fahrudin, Khaira Rizfia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Sales is the business activity undertaken by the company to make a profit. Companies try to find customers, provide information to customers regarding the products on sale, promote their products and hope that customers will be attracted and purchase. Companies need to apply strategy management, and appropriate actions to increase sales. The high or low of the sales rate can be affected by the product design and sales promotions that the company conducts. The product design improvement provided by the telecommunication provider companies in meeting the telecommunication needs of the public pioneered the growth of mobile phone business in Indonesia. The market share that was once dominated by manufactured products from Europe, has now been flooded with the entry of a wide range of mobile phone products from countries such as China, Thailand, Taiwan and South Korea. Even some mobile phone products from China and South Korea are taking over the market in Indonesia. One is the development experienced by Samsung mobile phones that as the existing technology development, slowly Samsung mobile phone products are able to shift the position of previously successful mobile phones such as Nokia, Sony Erricson, Motorola and Siemens. The look or product design created in Samsung products has the function of attracting consumers. With the presence of attractive and innovative designs it is expected to increase the buying interest of consumers towards the Samsung mobile products seen from its shape, model, color and various features.